Malaya’s greatest menace? Slow-onset disaster and the muddy politics of British Malaya, c. 1900–50 - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2018)
In 1948, a chilling statement from British Malaya’s Director of Agriculture, F. Burnett, made headline news. According to Burnett, unchecked soil erosion across hillside Malaya would soon render the country’s precious agricultural land infertile. Erosion had worsened considerably after the 1880s due to widespread, indiscriminate agricultural and industrial clearing. By the 1920s, it had become a sizeable socioeconomic and environmental issue, thought also to contribute to the scale and intensity of flooding and the likelihood of dangerous landslips. The British Government raised a series of empire-wide inquiries across the first half of the twentieth century, tied to an emerging global scientific interest in, and concern about, soil degradation, food security and economic productivity. The colonial British Government of Malaya—whilst acknowledging the part played by commercial agriculture—also tended to place blame on traditional shifting cultivators and farmers, especially the Chinese. This article discusses the problem of soil erosion in British Malaya as a primarily slow-onset disaster while also acknowledging erosion’s contributing role in more sudden hazards, such as landslips. It also explores how erosion was linked with an evolving blame culture in Malaya, involving discrimination against different social groups at different times. The narratives surrounding soil erosion thus offer a lens into the interplay of environment, colonialism and politics in British Malaya.